Reading Young Adult Literature for the Development of Self-Esteem Among Undergraduates in Malaysian Higher Education Institutions - Lourdunathan, Josephine (2010)
The purpose of this phenomenological study was to explore the potential of reading young adult literature in developing self-esteem among a group of undergraduates at a Malaysian higher education institution. Research on reading for self-development or bibliotherapy has demonstrated various gains with diverse population and problems. This study examined the effectiveness of reading young adult literature with a group of undergraduates with self-esteem issues. A qualitative methodology was employed to explore the participants reading of young adult literature at their natural setting. The data generated through interviews, dialogue journals and observations were able to present a rich in-depth data on the participants’ reading experience. Data were analyzed, tagged and coded based on common patterns which emerged from the study. Six undergraduates pursuing a degree in Bachelor of Education at Universiti Teknologi MARA, Melaka City Campus participated in the study. These participants read young adult literature, shared their thoughts, feelings and experiences on the reading phenomenon through dialogue journals. Data triangulation was carried by analyzing and comparing findings from observations made by two informants, researcher’s field notes, in-depth pre and post interviews and the administration of Rosenberg self-esteem questionnaire. The study discovered the undergraduates are aware of the importance of self-esteem and how their personal struggles have affected their level of self-esteem. Among the challenges faced by them are identity crisis, lack of self-confidence and poor family relationship The study also found that reading young adult literature has the potential to elevate the readers’ self-esteem. The reading process which involved the phases of connection-response-evolution has contributed to the success of developing self-esteem among the participants. This study uncovered four reading characteristics contributing to the effectiveness of reading young adult literature for self-esteem. Four types of reading characteristics – intentional, relational, reflective, transporting reflected the participants’ purposeful and conscious effort to seek help through reading of young adult literature while on participant showcased pleasure reading characteristic as he read for entertainment and information only. The findings of this study provided evidence that reading young adult literature can be inspiring and enriching. The participants revealed how the readings have helped them to understand their lives and the people around them. Reading young adult literature has helped them to experience a new level of self-confidence, gain new understanding of themselves, helped to feel less different and inspired them to grow positively. The results of this study may guide teachers and counselors in using young adult literature for helping young adult with self-esteem issues. The findings of this study suggest that literature can be used in schools for personal development and literature classroom has the potential to create authentic reading experiences. Literature can be a catalyst for growth and literature can be used as reading guidance in the educational institutions in Malaysia.